IDENTIFYING REASON TO FOLLOW OR UN-FOLLOW FOODBLOGGER REASON USING SEMI-STRUCTURED INTERVIEW - Iwantoro, Kimberly; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract. As Instagram platform explodes with influencer, food also becoming an unexpected battlefield, and resulted in rising up the number of food blogger. People can find food blogger from any source. There are several factors that will affect the following and un-following decision, which are foodblogger’s ‘attractiveness’, ‘trustworthiness’, and‘expertise’ as mentioned in the Source Credibility Model. This research used qualitative approach using semistructured interview. The highlight data also used quantitative approach by using online questionnaire to support the data by getting the average in each question. For the online questionnaire, data is collected from 100 respondents. Instagram feature contributes to the most used source in finding foodblogger compared to Internet source and referral. The more frequent high quality (photograph and review) posts, the lower unfollowing possibility. Mixed content with some stories outside food area, show person behind the account, tell the honest and same taste review compared to the actual condition, experienced in trying food, travelling and review the food outside Indonesia leads people to follow, while the unreliable one who tells review different compared to the actual condition leads people to unfollow. The more advertisements posted, the higher possibility of unfollowing. For the gender preferences, there’s no significant difference.Keyword: Follow, Foodblogger, Instagram, Source Credibility Model, Step, Un-follow